Utilization of maternal health services among young women in Kenya: Insights from the Kenya Demographic and Health Survey, 2003 - Ikamari Lawrence; Fotso Jean-Christophe; Ochako Rhoune; Khasakhala Anne (BMC, 2011)
Abstract Background Use of maternal health services is an effective means for reducing the risk of maternal morbidity and mortality, especially in places where the general health status of women is poor. This study was guided by the following objectives: 1) To determine the relationship between timing of first antenatal care (ANC) visit and type of delivery assistance 2) To establish the determinants of timing of first ANC visit and type delivery assistance. Methods Data used were drawn from the 2003 Kenya Demographic and Health Survey, with a focus on young women aged 15-24. The dependent variables were: Timing of first ANC visit coded as "None"; "Late" and "Early", and type of delivery assistance coded as "None"; "Traditional Birth Attendant (TBA)" and "Skilled professional". Control variables included: education, household wealth, urban-rural residence, ethnicity, parity, age at birth of the last child and marital status. Multivariate ordered logistic regression model was used. Results The study results show that place of residence, household wealth, education, ethnicity, parity, marital status and age at birth of the last child had strong influences on timing of first ANC visit and the type of delivery assistance received. The major finding is an association between early timing of the first ANC visit and use of skilled professionals at delivery. Conclusion This study confirms that timing of first antenatal care is indeed an important entry point for delivery care as young women who initiated antenatal care early were more likely to use skilled professional assistance at delivery than their counterparts who initiated ANC late. The results indicate that a large percentage of young pregnant women do not seek ANC during their first trimester as is recommended by the WHO, which may affect the type of assistance they receive during delivery. It is important that programs aimed at improving maternal health include targeting young women, especially those from rural areas, with low levels of education, higher parity and from poor households, given their high risk during pregnancy. The finding that a considerably high proportion of young women use TBAs as opposed to use of skilled professionals is baffling and calls for further research.